Penyuluhan kesehatan tentang jajanan sehat dan jajanan tidak sehat - Pribadi, Teguh; Keswara, Umi Romayati; Widodo, Slamet; Alparizi, Melki; Marlena, Leni; Pritasari, Laili; Wulandari, Hesti (JOURNAL OF Public Health Concerns, 2022)
Introduction: School Children Snacks conducted by the Food and Drug Supervisory Agency of the Republic of Indonesia Directorate of Food Inspection and Certification together with 26 supervisory agency/ the Food and Drug Supervisory Centers throughout Indonesia show that 45% of School Children Snacks do not meet the requirements because they contain hazardous chemicals such as formaldehyde, borax, rhodamine, and containing Food Additives such as cyclamate andbenzoate exceeds the safelimit. Purpose: Respondents can know, understand about healthy snacks and unhealthy snacks.                                                                                                                           Method: Implementation of the method used in counseling at Public Elementary School 1 Way Gubak is done by 3 stages, namely the first, students of the Psychology profession asking the difference between healthy and unhealthy snacks at, secondly, the presenters of Psychological students explained about healthy and unhealthy snacks using a Power point back, and the third asked questions related to the difference between healthy and unhealthy snacks after being explained. Results: Respondents understand about healthy and unhealthy snacks. Conclusion: Respondents can understand about healthy snacks and unhealthy snacks.   Pendahuluan: Jajanan Anak Sekolah (PJAS) yang dilakukan Badan Pengawas Obat dan Makanan (BPOM) Republik Indonesia Direktorat Inspeksi dan Sertifikasi Pangan bersama 26 Balai Besar / Balai POM di seluruh Indonesia menunjukkan bahwa 45% PJAS tidak memenuhi syarat karena mengandung bahan kimia berbahaya seperti formalin, boraks, rhodamin, dan mengandung Bahan Tambahan Pangan (BTP) seperti siklamat dan benzoat melebihi batas aman. Tujuan: Responden dapat mengetahui,Memahami tentang jajanan sehat dan jajanan tidak sehat. Metode: Pelaksanaan metode yang digunakan dalam penyuluhan di Sdn 1 Way Gubak ini dilakukan dengan 3 tahap, yaitu yang pertama mahasiswa profesi Psik menanyakan perbedaan jajanan sehat dan tidak sehat, yang kedua penyaji mahasiswa menjelaskan tentang jajanan sehat dan tidak sehat menggunakan Power point balik, dan ketiga tanya jawab terkait perbedaan jajanan sehat dan tidak sehat setelah di jelaskan. Hasil: Responden memahami tentang jajanan sehat dan tidak sehat. Simpulan:  Responden dapat memahami tentang Jajanan Sehat dan Jajanan tidak sehat.